Clinical Outcomes and Healthcare Utilization Related to Multidrug-Resistant Gram-Negative Infections in Community Hospitals. (11th October 2016) - Dicks, Kristen V.; Anderson, Deverick J.; Baker, Arthur W.; Sexton, Daniel J.; Lewis, Sarah S.
Abstract : OBJECTIVE: To evaluate the impact of multidrug-resistant gram-negative rod (MDR-GNR) infections on mortality and healthcare resource utilization in community hospitals. DESIGN: Two matched case-control analyses. SETTING: Six community hospitals participating in the Duke Infection Control Outreach Network from January 1, 2010, through December 31, 2012. PARTICIPANTS: Adult patients admitted to study hospitals during the study period. METHODS: Patients with MDR-GNR bloodstream and urinary tract infections were compared with 2 groups: (1) patients with infections due to nonMDR-GNR and (2) control patients representative of the nonpsychiatric, non-obstetric hospitalized population. Four outcomes were assessed: mortality, direct cost of hospitalization, length of stay, and 30-day readmission rates. Multivariable regression models were created to estimate the effect of MDR status on each outcome measure. RESULTS: No mortality difference was seen in either analysis. Patients with MDR-GNR infections had 2.03 higher odds of 30-day readmission compared with patients with nonMDR-GNR infections (95% CI, 1.04–3.97, P =.04). There was no difference in hospital direct costs between patients with MDR-GNR infections and patients with nonMDR-GNR infections. Hospitalizations for patients with MDR-GNR infections cost $5, 320.03 more (95% CI, $2, 366.02–$8, 274.05, P <.001) and resulted in 3.40 extra hospital days (95% CI, 1.41–5.40, P <.001) than hospitalizations for control patients. CONCLUSIONS: Our study provides novel data regarding the clinical and financial impact of MDR gram-negative bacterial infections in community hospitals. There was no difference in mortality between patients with MDR-GNR infections and patients with nonMDR-GNR infections or control patients. Infect Control Hosp Epidemiol 2016;1–8